Nanomaterials: Promising Tools for the Diagnosis and Treatment of Myocardial Infarction - Ge Y; Wu L; Mei S; Wu J (International Journal of Nanomedicine)
Yanmin Ge, Lincong Wu, Shuyang Mei, Junduo Wu Department of Cardiology, The Second Hospital of Jilin University, Changchun, Jilin, 130000, People’s Republic of ChinaCorrespondence: Junduo Wu, Email wujd@jiu.edu.cnAbstract: Myocardial infarction (MI) is the leading cause of mortality from cardiovascular diseases. Rapid diagnosis and effective treatment are critical for improving patient prognosis. Although current diagnostic and therapeutic approaches have made significant progress, they still face challenges such as ischemia-reperfusion injury, microcirculatory disorders, adverse cardiac remodeling, and inflammatory responses. These issues highlight the urgent need for innovative solutions. Nanomaterials, with their diverse types, excellent physicochemical properties, biocompatibility, and targeting capabilities, offer promising potential in addressing these challenges. Advances in nanotechnology have increasingly drawn attention to the application of nanomaterials in both diagnosing and treating myocardial infarction. We summarize the pathophysiological mechanisms and staging of myocardial infarction. We systematically review the applications of nanomaterials in MI diagnosis, including the detection of biomarkers and imaging techniques, as well as in MI treatment, encompassing anti-inflammatory effects, antioxidant stress, inhibition of fibrosis, promotion of angiogenesis, and cardiac conduction repair. We analyze the existing challenges and provide insights into future research directions and potential solutions. Specifically, we discuss the need for rigorous safety assessments, long-term efficacy studies, and the development of robust strategies for translating laboratory findings into clinical practice. In conclusion, nanotechnology holds significant promise as a new strategy for diagnosing and treating myocardial infarction. Its potential to enhance clinical outcomes and revolutionize patient care makes it an exciting area of research with practical applications in real-world clinical settings.Keywords: myocardial infarction, nanomaterials, nanoparticles, diagnosis and treatment